Lampi di possibili tempeste. Arte e letteratura nel Foucault degli anni Settanta. (ENTHYMEMA, 2012)
References to visual arts and literature seem to lose their centrality in Foucault’s oeuvre, after holding a paramount importance in his 1970s archaeological writings. This change corresponds with Foucault’s shift from main works to shorter contributions, wherein his own subjective involvement becomes the core of the theoretical reflection. However, this turning point must also be seen as a radical reassessment of the historical and ontological function that Foucault had previously attributed to literature. Overcoming this view, in fact, the French philosopher moves towards non-strategical forms of experience that are not limited to the power-resistance relationship. These new modalities of experience, this paper argues, can be understood as a critique -and possibly a political critique- of the relationship between historical temporality and the transformation of subjectivity.